Significant changes to the international building code 2021 - Thornburg, Douglas W.; Hyde, Sandra; Woodward, Jay (New York McGraw-Hill, 2021)
Gain full access to over 155 of the most significant changes to the International Building Code, including the real-world application of those changes and how they originated ? all in a single, easy-to-use resource. SIGNIFICANT CHANGES TO THE INTERNATIONAL BUILDING CODE 2021 Edition provides a comprehensive analysis of significant changes since the 2018 IBC , offering key insights into its contents and implications. Coverage includes changes made to both structural and non-structural provisions. Each change analysis features the affected code sections and identifies the change with strikethroughs and underlines to show modifications to the existing language. Each change is accompanied by a quick summary, detailed illustrations, and discussion of its significance, which brings the technical jargon of the code to life in a real-world setting. The attention to detail, logical organization, and thorough yet concise coverage found in this resource make it an ideal tool for transitioning from the 2018 IBC.
Electronic reproduction
Keywords: Construction industry -- Standards; Standards, Engineering; Building laws; Buildings -- Standards; Electronic books